Physiochemical, Bio, Thermal, and Non-Thermal Processing of Major and Minor Millets: A Comprehensive Review on Antinutritional and Antioxidant Properties - Suhan Bheemaiah Balyatanda; N. A. Nanje Gowda; Jeyamkondan Subbiah; Snehasis Chakraborty; P. V. Vara Prasad; Kaliramesh Siliveru (Foods)
Millets are recognized as future foods due to their abundant nutrition and resilience, increasing their value on the global stage. Millets possess a broad spectrum of nutrients, antinutrients, and antioxidants, making it imperative to understand the effects of various processing methods on these components. Antinutritional factors interfere with the digestibility of macro-nutrients and the bioavailability and bio accessibility of minerals. This necessitates methods to reduce or eliminate antinutrients while improving nutritive and antioxidant value in food. This review aims to elucidate the rationale behind processing choices by evaluating the scientific literature and examining the mechanisms of processing methods, categorized as physiochemical, bio, thermal, novel non-thermal, and their combination techniques. Physiochemical and bioprocessing methods alter antinutrients and antioxidant profiles through mass transfer, enzyme activation, product synthesis, microbial activity, and selective removal of grain layers. Thermal methods break functional bonds, modify the chemical or physical structures, enhance kinetics, or degrade heat-labile components. Non-thermal techniques preserve heat-sensitive antioxidants while reducing antinutrients through structural modifications, oxidation by ROS, and break down the covalent and non-covalent bonds, resulting in degradation of compounds. To maximize the trade-off between retention of beneficial components and reducing detrimental ones, exploring the synergy of combination techniques is crucial. Beyond mitigating antinutrients, these processing methods also stimulate the release of bioactive compounds, including phenolics, flavonoids, and peptides, which exhibit potent health-promoting properties. This review underscores the transformative potential of processing technologies in enhancing millets as functional ingredients in modern diets, promoting health and advancing sustainable food practices.